Optimizing Customer Data Security in Water Meter Data Management Based on RESTful API and Data Encryption Using AES-256 Algorithm - Adrianto, Syahrul; Agus Herlambang, Bambang; Renaldy, Ramadhan (Journal of Applied Informatics and Computing, 2025)
Good, accurate and secure data management is certainly one of the main needs for companies that provide public services. This research aims to develop a web application-based information system to manage customer water meter data at a regional water company in Semarang. This system was built using the RESTful API architecture using the PHP programming language framework, namely Laravel and the development of web page displays using the Javascripts framework. The data used is the original database managed by the company every month which is managed using a database management system by meter reader officers. To increase the security of customer data, a cryptographic algorithm is used, namely the Advanced Encryption Standard (AES) algorithm with a 256-bit key length to secure data that is considered sensitive and contains high privacy. This system is intended for meter readers to update customer water meter data per month in an efficient and structured manner. This research uses a Research and Development (R&D) based software development method with system testing using black-box testing method to ensure application functionality and data exposure testing method to ensure data security in the database. The test results show that the system successfully manages customer water meter data in realtime per data sent and secures customer data.